Urban Land and Sustainable Development (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
According to the 2014 revision of the World Urbanization Prospects by UN DESA, urbanization could add another 2.5 billion people to urban population by 2050, with close to 90 percent of the increase concentrated in Asia and Africa. This unprecedented increase in urban population not only poses challenges to providing jobs, housing, and infrastructure, but also exerts an increased pressure on urban land and sustainability. As land is a vital yet limited resource, sustainable management of urban land to cater the needs of this growing urban population is seen as one of the key challenges for achieving an economically efficient, socially equitable, and environmentally safe society. A key tenet for sustainable economic development and smart growth is promoting equitable sustainable urban land development and mitigating land use conflicts. While a large body of literature has dealt with both land use and sustainable development, the study of the interactive effects of these two remains limited. We need more sophisticated empirical studies examining processes, mechanisms, institutions, equity, and sustainability of urban land use. This book is based on a Special Issue published in Sustainability, and examines patterns, structure, and dynamics of urban land development and sustainability from multiple perspectives, in various contexts and at multiple dimensions (economic, social, political, developmental, and environmental, etc.). The research articles examine urban land development and sustainability arising from globalization, urbanization and institutional change. We have drawn papers from both developed and developing countries, with a focus on China due to the rapid rate of urbanization and change there. This book includes 14 articles, with various research emphases, methodologies and study areas, reflecting the inter-disciplinarily that characterizes urban and land use studies. The book has examined patterns and processes of urban land expansion and sprawl, and also studies new dimensions of urban space, including social media. These papers can provide us insights into the underlying structure and mechanisms of urban land expansion, and open new frontiers on the effects of urban land development on both the natural and human environments. We hope that this book will contribute to the understanding of urban land use patterns and processes, and their implications for sustainable development.